Shifting Sands? Citizens' National Identities and Pride in Social Security in Canada. - Raney, Tracey; Berdahl, Loleen (American Review of Canadian Studies, 2011)
While the use of public policy to construct a Canadian identity has been established in the literature, what is less well understood is whether national identity, once established, might shape Canadians' feelings about these same public policies. This article examines the extent to which citizens' national identities influence their pride in Canada's social security system, and how this relationship may be changing over time. Using data from the International Social Science Programme's 1995 and 2003 National Identity Modules, the article argues that citizens' national identities help explain the contours of social security attitudes in Canada, and that this relationship persists despite significant policy change in the field. Additionally, the paper suggests that political actors may successfully increase public support for their social security policies by “framing” them in ways that appeal to citizens' definitions of Canada.